2003
DOI: 10.1093/hmg/ddg196
|View full text |Cite
|
Sign up to set email alerts
|

Morpholino antisense oligonucleotide induced dystrophin exon 23 skipping in mdx mouse muscle

Abstract: The mdx mouse model of muscular dystrophy arose due to a nonsense mutation in exon 23 of the dystrophin gene. We have previously demonstrated that 2'-O-methyl phosphorothioate antisense oligonucleotides (AOs) can induce removal of exon 23 during processing of the primary transcript. This results in an in-frame mRNA transcript and subsequent expression of a slightly shorter dystrophin protein in mdx muscle. Refinement of AO design has allowed efficient exon skipping to be induced in mdx mouse muscle cultures at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(128 citation statements)
references
References 35 publications
1
125
1
1
Order By: Relevance
“…Although AO concentrations below 300 nM and at time-points beyond 24 h were useful in many cases, selecting a single concentration of 300 nM and a time-point of 24 h permitted effective comparison. By contrast to a number of previous studies [2,23], in vitro splice correcting activity was demonstrated for unmodified PNA and PMO Aos, as well as for peptide conjugated versions of these compounds. Importantly, use of the optimized in vitro parameters allowed comparative AO activity to be determined by measuring the percentage of skipped DMD transcript at the RNA level.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Although AO concentrations below 300 nM and at time-points beyond 24 h were useful in many cases, selecting a single concentration of 300 nM and a time-point of 24 h permitted effective comparison. By contrast to a number of previous studies [2,23], in vitro splice correcting activity was demonstrated for unmodified PNA and PMO Aos, as well as for peptide conjugated versions of these compounds. Importantly, use of the optimized in vitro parameters allowed comparative AO activity to be determined by measuring the percentage of skipped DMD transcript at the RNA level.…”
Section: Discussioncontrasting
confidence: 98%
“…The earliest demonstrations of successful AO-induced exon skipping of the dystrophin were demonstrated in vitro in human lymphoblastoid and mdx mouse muscle cells [18,21], skipping DMD exons 19 and exons 22-30, respectively. Subsequently, numerous in vitro exon skipping studies have been undertaken demonstrating precise skipping of DMD exon 23 in mdx mouse muscle cells [29] with protein correction in mdx mice in vivo [6]; successful DMD exon 46 skipping in patient-derived muscle cells [22]; further mdx exon 23 2 OMePS sequence refinement and evaluation of AO concentrations [30]; evaluation of 'leashed' PMO AOs [23]; the comparative effects of different 2 OMePS, PMO, PNA and LNA AOs for skipping DMD exon 46 in human muscle cells [2]; the influence of AO length on AO splice correcting efficacy [31]; optimization and selection of a human DMD exon 51 skipping AO for clinical trial [32]; and the exon skipping activity of PNA and PNApeptide AOs in mdx muscle cells [8,13,14]. Despite these and other in vitro studies, little agreement exists on the optimal parameters for in vitro AO screening, no studies to date have compared across different AO backbone chemistries and AO-peptide modifications, and little if any data exist on the value of in vitro screens as predictors of in vivo AO activity across a wide range of AO compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment induces removal of exon 23 during processing of the primary transcript and results in expression of a slightly shorter dystrophin protein (18). Similar therapy is being administered to Duchenne muscular dystrophy patients in clinical trials with excellent results demonstrated as maintaining ambulation (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Sections from untreated mdx and wt mice are included for comparison. All images were captured and processed by using identical parameters (18,40). Dystrophin protein was assessed on immunoblot as described (40,41).…”
Section: Methodsmentioning
confidence: 99%